EFEKTIFITAS LATIHAN BERDASARKAN PROSES LATIHAN PADA FITNESS CENTER DAN PADA KLUB OLAHRAGA - eki aldapit (Jurnal Muara Olahraga, 2019)
This article was written to (1) the effectiveness of training 3x a week and 4x a week based on the training process at the fitness center and sports club. (2) the difference in the effectiveness of weight training with a frequency of 3x a week and 4x a week. This study aims to determine whether there is a difference in the effectiveness of weight training with 3x workouts a week and 4x week training on muscle hypertrophy.The approach used in data retrieval is a literature review approach with descriptive methods. Based on the analysis of the results of the research and discussion, it can be concluded that weight training with a frequency of 4 times a week of exercise is more effective than the frequency of 3 times a week training based on public exercises and exercises carried out in training programs carried out in official sports development.